Relationship between Carotid Intima-Media Thickness and Left Ventricular Hypertrophy - Yusrina Saragih; Harris Hasan; Zainal Safri; Zulfikri Mukhtar; Refli Hasan; Nizam Akbar (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2019)
Background: Hypertension is a 50% cause of cardiovascular disease and stroke, 40% of cause of death in Diabetics, and is a major risk of kidney failure, pregnancy and dementia. Left ventricular hypertrophy (LVH) is a preclinical manifestation of cardiovascular disease and a strong predictor of cardiovascular morbidity and mortality. Examination of carotid intima-media thickness (CIMT) is one method that can be used to Evaluate the occurrence of coronary heart disease and in Several studies reported that CIMT is also associated with left ventricular function and hypertrophyMethods: This cross-sectional study conducted on hypertensive patients in the outpatient unit in Cardiac Center Haji Adam Malik General Hospital since March 2018-August 2018. Examination of Carotid B-Mode ultrasound was conducted to obtain CIMT values. LVH is assessed by left ventricle mass index (LVMI) as measured by M-mode method using the Cube formulas from echocardiography. Then the analysis is done using the Spearman correlation test to see the relationship between CIMT and LVHResults: The CIMT >0.5 mm have a positive correlation with LVM (r = 0.594, p <0.001), LVMI (r = 0.618, p <0.001), RWT (r = 0.364, p <0.001), and LVH (r = 0484, p <0.001). The CIMT >0.5 mm has a sensitivity of 83.6%, specificity 90.4%, PPV NPV 76% and 93.8%. The CIMT value of 0:55 mm is considered to be the optimal value in diagnosing LVH in hypertensive patients in our subjects based on the ROC curve with a sensitivity of 83.6% and specificity of 90.5%, and area under the curve of 0.9.Conclusion: There is a positive correlation between carotid intima-media thickness and left ventricular hypertrophy in hypertensive patients